Correlation Analyze Between Working Environment and Reward With The Employee Motivation PT. Waskita Beton Precast Tbk. In Jakarta - Carolus Kinarsih Lwanga Tindra Matutino Kinarsih (UniSadhuGuna Business School, 2019)
In the globalization era with volatile and uncertaintay ambience highly productive employee with high motivation and creativity is the core process to running the infrastructure company. This study aims to analyze the correlation of working environment and reward to the employee motivation in PT. Waskita Beton Precast Tbk. Jakarta. Hypothesis testing was carried out by distributing questionnaires to 50 responses. The analyze used is the result of the validity test, the reliability test, the regression analyze test (multiple collinearity test, heteroscedasticity, normality test), and the hypothesis test using multiple linear regression analysis (t test, f test, and model summary) with the aid of SPSS version 22 computer. By using multiple regression analysis method, it is concluded that working environment variable has /correlation to employee motivation, and there is acorrelation for reward variable to employee motivation. While Variable of work environment and reward simultaneously have an influences to employee motivation variable at PT. Waskita Beton Precast Tbk. Jakarta.